The difficulties of implementation of BIPV in Portugal, rejection or abstention? - Jesus, Luciana (2005)
The position of Portugal in the context BIPV is negative and controversial. While some countries identified with odd or difficult conditions for the spread of these systems, succeeded in overcoming the constraints and are increasing using them, Portugal, with one of the highest solar radiation levels within Europe, is not seriously considering their one. One must ask, “What hinders the penetration of the BIPV system into the Portuguese market?” The purpose of this work is to try to get an answer to this question. First, it will define the concept; the characteristics and the advantages of BIPV applications in Mediterranean countries. After, it will define the reasons that justify the difficulty of BIPV development into the Portuguese market. Then it will discuss the most recent measures that are being consolidated in Portugal in order to invert the actual situation. This includes ongoing private projects and public investigation developed in Universities. In the end, it will be presented a case study of a BIPV application to a Portuguese Hotel, focusing on witch allows the viability of these applications.